Karakter Pemilih Pemula di Kabupaten Tuban: Adaptasi Budaya Politik Sekolah - Hasanul Bulqiyah; Dwi Wahyu Kartikasari; Petrus Ans Gregorius Taek (Universitas Indo Global Mandiri, 2023)
Starting from curiosity about how the political culture of the school in shaping the character of novice voters in Tuban Regency. So this research was conducted using comparative qualitative methods to explore primary data on research subjects spread across senior high schools (SMA) in Tuban Regency such as Deputy Head of Student Affairs, Citizenship Education Teachers, Coaches and OSIS Students (Intra-School Student Organizations), including the General Election Commission of Tuban Regency as secondary data in this study. The results showed that the political culture of schools in shaping the character of novice voters in Tuban Regency with an understanding and emphasis on students about politics in Indonesia through classroom teaching, then the implementation of democracy in Indonesia in the OSIS election, as well as school innovation in carrying out the student council selection process that is packaged online. Furthermore, the adaptation of political culture that is applied forms the character of students as novice voters. The character of students as novice voters is behavior that is active in practical politics, starting from following, criticizing and participating. This active behavior can be seen from the implementation of the smallest political practice in schools, namely the Student Council Election.